Determination of hyaluronic acid in pharmaceutical products by spectrophotometry and HPLC coupled to fluorescence or mass spectrometric detection - Kašparová, Jitka; Arnoldová, Kamila; Korecká, Lucie; Česlová, Lenka (University of Pardubice, 2018)
In a daily basis, the pharmaceutic and cosmetic industry makes effort in advertising their products with a promise to avoid diseases or health problems. Among one of the most popular substances is nowadays, without doubts, hyaluronic acid (HA). Due to its natural origin allowing its biodegradability and non-toxicity, HA is widely used as a component of joint supplements or as a substance ensuring moisturizing properties. Here, interest is focused on the determination of hyaluronic acid in commonly available non-prescription products using different analytical techniques followed by comparison of the determined content with that declared by manufacturers.
Keywords: hyaluronic acid; supplements; high-performance liquid chromatography; spectrophotometry; mass spectrometry